2017
DOI: 10.1016/j.celrep.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Medial and Lateral Entorhinal Cortex Differentially Excite Deep versus Superficial CA1 Pyramidal Neurons

Abstract: SUMMARY Although hippocampal CA1 pyramidal neurons (PNs) were thought to comprise a uniform population, recent evidence supports two distinct sublayers along the radial axis, with deep neurons more likely to form place cells than superficial neurons. CA1 PNs also differ along the transverse axis with regard to direct inputs from entorhinal cortex (EC), with medial EC (MEC) providing spatial information to PNs toward CA2 (proximal CA1) and lateral EC (LEC) providing non-spatial information to PNs toward subicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
121
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(146 citation statements)
references
References 56 publications
22
121
0
Order By: Relevance
“…CA3 Schaffer collateral excitation is stronger in calbindin-positive, superficially located CA1PCs. Note that proximodistal differences in cortical innervation between radial sublayers have also been reported 93,94 (not shown). PVBCs (green) provide stronger perisomatic inhibition onto deep CA1PCs and receive stronger excitation from superficial CA1PCs.…”
Section: Figmentioning
confidence: 55%
See 2 more Smart Citations
“…CA3 Schaffer collateral excitation is stronger in calbindin-positive, superficially located CA1PCs. Note that proximodistal differences in cortical innervation between radial sublayers have also been reported 93,94 (not shown). PVBCs (green) provide stronger perisomatic inhibition onto deep CA1PCs and receive stronger excitation from superficial CA1PCs.…”
Section: Figmentioning
confidence: 55%
“…In this pathway, MEC and LEC project to different parts of CA1 along the proximodistal axis, leading to differential recruitment of PCs along this axis during spatial and nonspatial tasks 47,75,76,78,80,91,92 . A recent study 93 found that these two inputs also activate the radial CA1PC sublayers differentially (Fig. 3a) and that this differential innervation varies as a function along the proximodistal axis.…”
Section: Functional Heterogeneity Of Ca1pc In the Context Of Behaviormentioning
confidence: 84%
See 1 more Smart Citation
“…For example, dorsal and ventral entorhinal cortex (EC) predominately innervate dorsal and ventral CA1, respectively, and via the EC, dorsal hippocampus receives more input from anterior cingulate and retrosplential cortex, while ventral hippocampus receives more input from infralimbic and prelimbic cortices [52]. Modified with permission from [58]. (c) Illustration highlighting experiments in which changes in grid cell representations were associated with altered place cell activity.…”
Section: Figurementioning
confidence: 99%
“…Differences in afferent connectivity likely contribute: deep CA1 place cells receive stronger excitation from CA2, superficial CA1 place cells receive stronger excitation from CA3 [53 • ], and the extent of MEC and LEC drive to CA1 varies across both the radial and transverse axes (Figure 1) [58,59]. However, it is also possible that differences in single-cell intrinsic biophysical properties and the genetic expression profiles that underlie such biophysics contribute.…”
Section: Introductionmentioning
confidence: 99%